BS EN IEC 60794-1-401. Optical fibre cables. Basic optical cable test procedures. Part 401. Electrical test methods. Short-circuit test (for OPGW, OPPC and OPAC), Method H1 (19th February 2020) - British Standards Institution,
No abstract available